Implementation of Tourism Sector Development Policy through Demarketing in Improving SME in Banyuwangi - Irawan, Ari (International Journal of Social and Local Economic Governance, 2017)
The successful development of the tourism industry creates direct and indirect economic impact, as well as spillover, that drives the SMEs and the economy. In 2011, tourism became the fifth largest contributor of foreign exchange, consequently increasing the tourism sector is also expected to grow the SME sector. Stakeholders involved include the government as a regulator policy, community, and SMEs to support the tourism sector. This study aims to determine the implementation of tourism policy in Banyuwangi and the impact of these policies on the SME sector. This study used a qualitative approach; data collection is by interview, documentation, and literature. The results show that the cornerstone of the planning and implementation of tourism programs in Banyuwangi covers the tourism industry, tourism destinations, and tourism institutions; tourism and marketing have been executed better. The implementation of the demarketing strategy brings positive impact on the preservation of nature, so the concept of responsible and sustainable tourism can be realized. In addition, based on the data of SMEs rural areas, tourist sites show positive trend from year to year. The demarketing strategy is successful in supporting the potential of SMEs to thrive in Banyuwangi.Keywords: Implementation of Demarketing, SME Development, Tourism DevelopmentÂ